2016
DOI: 10.1007/978-3-319-27671-7_71
|View full text |Cite
|
Sign up to set email alerts
|

Using Instagram Picture Features to Predict Users’ Personality

Abstract: Instagram is a popular social networking application, which allows photo-sharing and applying different photo filters to adjust the appearance of a picture. By applying these filters, users are able to create a style that they want to express to their audience. In this study we tried to infer personality traits from the way users manipulate the appearance of their pictures by applying filters to them. To investigate this relationship, we studied the relationship between picture features and personality traits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 29 publications
9
70
1
1
Order By: Relevance
“…Other previous works predicted personality traits from Instagram pictures [14] (with a Root Mean Square Error ranging from 0.66 for Conscientiousness to 0.95 for Neuroticism) and from profile pictures of 100 Facebook users, obtaining an average F1-measure of 67% [5]. An important issue with personality prediction is the relationship between self-assessed and observer-perceived personality types.…”
Section: Related Workmentioning
confidence: 99%
“…Other previous works predicted personality traits from Instagram pictures [14] (with a Root Mean Square Error ranging from 0.66 for Conscientiousness to 0.95 for Neuroticism) and from profile pictures of 100 Facebook users, obtaining an average F1-measure of 67% [5]. An important issue with personality prediction is the relationship between self-assessed and observer-perceived personality types.…”
Section: Related Workmentioning
confidence: 99%
“…The contributions of this work to personality research comes in two fold: 1) we extend prior research by Ferwerda et al [11,13] by exploring the predictive value of personality in the content features of Instagram pictures, and 2) we explore whether combining visual features with content features improves personality prediction of Instagram users.…”
Section: Introductionmentioning
confidence: 97%
“…1 With the use of picture filters, Instagram allows its users to create and express a distinct personal style by adjusting and manipulating the appearance of the content they want to share. Previous work of Ferwerda et al [11,13] on predicting personality traits from Instagram pictures extracted the visual features of Instagram pictures and showed that these properties consist of personality information of users. A few other work showed that personality can be predicted from pictures.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly as the case of personality perception, personality recognition have been addressed in the literature using different data modalities, i.e., still images [50], [96], [97], image sequences [98], [99], audiovisual (with [11], [59], [79], [85], [86], [100], [101], [102], [103] or without [88], [104] interactions) and multimodal [105], [106], [107], [108].…”
Section: Automatic Personality Recognitionmentioning
confidence: 99%
“…Taking the popularity of social networks into account, Ferwerda et al [96] proposed to infer real personality from the way users manipulate their pictures on Instagram. However, the work is basically limited to color information analysis.…”
Section: Automatic Personality Recognitionmentioning
confidence: 99%